NEW APPROACH TO DETERMINING THE ECONOMIC POTENTIAL OF RURAL AREA ON THE EXAMPLE OF THE SOUTH BOHEMIAN REGION OF THE CZECH REPUBLIC - Pártlová, Petra; Dvořáková Líšková, Zuzana; Felcan, Miroslav; Straková, Jarmila; Váchal, Ján; Polomský, Jozef (Entrepreneurship and Sustainability Agency, 2020)
The paper discusses a new approach to determining the economic potential of rural area on the example of the region of South Bohemia in the Czech Republic. The approach is based on a comprehensive economic model, consisting of four sub-models (SM). Such aggregate model is used as the basis for the analysis of regional economic potential. The SMs were defined by the Progressivity Index of the Economic Structure, Trend of the Economic Structure Index, Business Activity Rate and Recreation and Tourism Index. The mathematical-statistical method of Stepwise backward analysis was used as an analytical tool. During this stage, the data database from Ekotoxa was used. Practically, the first two SMs named were verified. Furthermore, the implementation of the results was designed and tested by the researchers. Two research objectives were fulfilled, namely the construction of summary and partial models, and the suitability of the analytical method tested are verified. Practical knowledge to deal with the situation in the region of South Bohemia was also obtained. The positively influencing factors for the economic potential of the region include the trend of increasing the number of people with university education, public transport services on weekdays, nursery facilities and population density. Negative factors include the natives and availability of secondary schools with the Maturita exam and landscape fragmentation. Within the mathematical modelling, it is possible to simulate the positive and negative response of additional inputs to the tested factors.
Nový přístup ke stanovení ekonomického potenciálu venkovské oblasti na příkladu Jihočeského kraje v České republice
Keywords: economic potential; rural space; Stepwise backward analysis; Summary economic model; Sub-model; ekonomický potenicál, rurální prostor, Souhrnný ekonomický model; Submodel